Estratégias de significação no jornalismo on-line: o espanto em narrativas dramáticas - Sardinha, Gabriela Pavanato (2015)
The general aim of this work is to study the manifest of dramatic narratives and their signification in the news portals. Specifically, it queries how the new information flows distribute their content in virtual environments and how this composition interferes in the signification of the reported facts. Our hypothesis suggests the online mosaics add a second level to the texts, reaffirming stereotypes, starting from the verbal and visual composition of their homepages. The investigation focuses on the observation of fait divers , whose signification is supported by the mix of fictional narratives with the reality and the relationship of these with serials, nineteenth-century genre that reappears, compressed, in the portals footers. The research corpus is composed of free and open websites, G1 and UOL, selected between 2012 and 2014. The methodology is based on the understanding of the syncretic object from the perspective of Discursive Semiotics, preceded by a bibliographical and documental survey, with systematic monitoring of those medias. Theoretically, we have adopted the A. J. Greimas Semiotic models, the classic work developed for the press by Roland Barthes, especially his ideas on the narrative movement of the news when dealing with the fait divers and myth , and the Marshall McLuhan s interpretation for the media organization as a mosaic. We also bring along the concept of journalistic field, defined by Pierre Bourdieu, to analyze the struggles it accomplishes to acquire visibility